Development of a Simple Method for the Specific Detection of Anthrax Antibody in Sera by Colored Slide Agglutination Test (Research in Agriculture Livestock and Fisheries, 2020)
This study was aimed to identify humoral immune response against anthrax vaccine in mice model by using colored slide agglutination test and detection of field infectivity of anthrax. The field isolates of B. anthracis (n=05) and F34 stern strain vaccine was isolated on agar plates in order to carry out the slide agglutination test. The field isolates of B. anthracis and vaccine bacteria grew on PLET agar medium produced roughly circular and creamy white colonies with ground glass appearance. The bacteria on sheep blood agar media produced rough, sticky, white-gray non hemolytic colonies. Colony polymerase chain reaction (PCR) protocol was adapted to detect fragments of pX01 (596bp) and pX02 (777bp) plasmid of virulent field isolates of B. anthracis. The fragment of pX01 plasmid was only detected in vaccine bacteria. Growth of a field isolate and a vaccine bacteria were colored with crystal violet and used in slide agglutination test to detect anthrax antibodies. The anti-anthrax antibody was prepared by immunizing female mice with 100ül anthrax vaccine through subcutaneous route. Tail bleed were collected on day 0, 30, 60, 120 and 180 of immunization. Cardiac bleed was collected on day 180 of immunization for extensive study. 25μl of diluted (1:10, 1:20, 1:50 and 1:100) antisera and 25μl colored antigen was mixed together onto a clean slide at room temperature and the results was red following 5min, 10mins, 15mins and 20mins of reaction. Unstained antigens and non-immunized sera from the mice were used as control. Results of slide agglutination test showed that the colored vaccine bacteria and field isolates clumped the mice anti-antisera (day 30, 60, and 120) at 1:20 dilution as seen in naked eye but the reaction was seen only at 1:10 dilution while colorless antigens were used. Under microscopic investigation of slide agglutination test, the reaction was read up to 1:100 dilutions with the sera collected at day 30, 60, 120 and 180 of immunization. The Anthrax Sterne strain vaccine induced anti-anthrax immunity in mice that was detected until day 180 of immunization. The clumping reaction was distinct while colored anthrax antigen was used in slide agglutination tests. The colored slide agglutination tests protocol developed in this study can be used to detect anti-anthrax immune response and anthrax bacteria in the field condition with minimum laboratory facilities.Res. Agric., Livest. Fish.7(3): 497-506,  December 2020